Edukasi Modul Sumping (Support Suami Pendamping) Sebagai Persiapan Persalinan Bagi Ibu Dan Calon Pendamping Persalinan - Rullyni, Nurniati Tianastia; Dewi, Utami; Putri, Sabtini Ika (Borneo Community Health Service Journal, 2025)
The presence of the husband as a labor companion plays a crucial role as it can create a sense of safety and comfort, boost the mother's confidence, reduce anxiety about the childbirth process, lessen labor pain intensity, decrease childbirth complications, and speed up the labor process. Therefore, efforts to improve the knowledge and attitude of husbands in labor companionship through the "SUMPING" (Support Suami Pendamping) Module are necessary. The goal of this community service activity is to enhance the knowledge and attitude of husbands in labor companionship. The method used involves providing education/counseling through the module, leaflets, video screenings, and proper labor companionship simulation/practice. The evaluation includes pre-tests and post-tests, as well as blood pressure checks for the mother. The target participants of this activity are 30 pregnant women and their husbands (prospective labor companions). The event will take place in Kelurahan Pinang Kencana, Puskesmas Batu 10. The time of implementation is from June to November 2024.Results: There was an increase in the knowledge of pregnant women and their husbands (prospective labor companions) before and after the education using the module. Suggestions: It is hoped that pregnant women and their husbands (prospective labor companions) will be able to prepare for childbirth by implementing the role of labor companion, utilizing the module as a medium to enhance knowledge, and increasing husband participation in childbirth accompaniment to prevent complications.